Efektivitas Pelatihan Regulasi Emosi untuk Menurunkan Stres Kerja pada Anggota Reskrim - Putri Pusvitasari; Hepi Wahyuningsih; Yulianti Dwi Astuti (JIP (Jurnal Intervensi Psikologi), 2016)
The study examined the effectiveness of emotion regulation training to reduce criminal policeman's work stress. This study used a pretest-posttest control group design. The participants were 13 criminal policemen from two different police stations, namely Polda X and Polsek Y. They were men and women aged between 20 - 50 years old, and classified into two groups. One group (n = 6) received emotion regulation training as the experimental group and the other (n = 7) as controlled group (waiting list). Participants were assessed using work stress scale that had been adapted from Abras (2012) research. The result showed that there was a significant difference in the implementation of posttest between the experimental and control group. By using mann whitney, the result concluded that emotion regulation training was significantly effective to reduce work stress of criminal policeman (Z = -2,006, p = 0,045, where p < (0,05).Key words : work stress, emotion regulation training